IMPLEMENTATION OF STUNTING PROGRAM IN INDONESIA: A NARRATIVE REVIEW - Siti Zaleha; Haerawati Idris (Universitas Airlangga, 2022)
Background: Stunting is one of the nutritional problems in the world, especially in Indonesia. Aims: This study aimed to describe the implementation of stunting programs in Indonesia, Related to specific and sensitive nutrition interventions in particular. Methods: This narrative review was conducted with a meta-synthetic approach. The literature search was done on Google Scholar, PubMed, Garuda Portal, and DOAJ. The critical appraisal checklist from the Joanna Briggs Institute (JBI) was used to assess the research quality. Results: Thirteen research articles were analyzed, and some intervention programs most commonly carried out were the provision of iron supplement tablets for pregnant women, supplementary feeding for underweight toddlers, complementary foods for breastfeeding, vitamin A provision, provision of facilities, access to drinking water, and proper sanitation. Conclusion: The stunting program has not been implemented optimally either inside or outside the health sector. Sufficient numbers of human resources, especially nutritionists, are required to realize stunting programs.